Konsumsi Makanan Siap Saji Sebagai Faktor Dominan Terjadinya Dismenore Pada Remaja : The Consumption of Fast Food as a Dominan Factor to Occurring Dysmenorrhea of the Adolescent - Ida Kusumawati; Umi Aniroh (Journal of Holistics and Health Sciences (JHHS), 2020)
Dysmenorrhea or menstrual pain is one of problems that is often complained adolescent. The purpose of the insulation is to know the most dominant factor related to the incident of dysmenore in adolescent. This type of research is an analytical observational research with cross sectional design. Sample research of 108 people taken by purposive sampling. The research instruments used are questionnaires. Analysis using Chi-square and logistic regression. Results show the average age of respondents was 13-17 years old. Most adolescent 86 (79.6%) aren’t do exercise regularly the majority of teenagers experience mild stress as much as 58 people (53.7%), adolescent often consume fast food as many as 76 people (70.4%) and adolescents experienced a dysmenore occurrence of 81 people (75.0%). Results gained that there is a relationship between sports habits and dysmenore events with Pearson chi-square p = 0,168 ≤ α (0.05), there is a link between stress levels with a dysmenore occurrence with Pearson chi-square p = 0, 070 ≤ α (0.05), there is a connection between fast-consumption with a dysmenore event with Pearson chi-square p = 0, 000 ≤ α (0.05). The final result obtained that affect the incidence of dysmenore is the consumption of fast food. Advice for the adolescent further expands the knowledge of dysmenrhea so that when experiencing dysmenore events can overcome it. ABSTRAK Dismenore atau nyeri menstruasi merupakan salah satu masalah yang sering dikeluhkan remaja. Tujuan penelitian ini untuk mengetahui faktor paling dominan yang berhubungan dengan kejadian dismenore pada remaja. Jenis penelitian ini adalah penelitian observasional analitik dengan desain cross sectional. Sampel penelitian sebanyak 108 orang yang diambil dengan cara purposive sampling. Instrumen penelitian yang digunakan adalah kuesioner. Analisis data menggunakan chi-square dan regresi logistik. Hasil penelitian menunjukkan umur responden berkisar antara 13-17 tahun. Sebagian besar remaja 86 (79,6%) tidak melakukan olahraga dengan teratur, sebagian besar remaja mengalami stres ringan sebanyak 58 orang (53,7%), remaja sering mengkonsumsi makanan cepat saji sebanyak 76 orang (70,4%) dan remaja mengalami kejadian dismenore sebanyak 81 orang (75,0%). Ada hubungan antara kebiasaan olahraga dengan kejadian dismenore dengan p= 0,168 ≤ α (0,05), ada hubungan antara tingkat stres dengan kejadian dismenore dengan p= 0, 070 ≤ α (0,05), ada hubungan antara konsumsi makanan cepat saji dengan kejadian dismenore dengan p= 0, 001 ≤ α (0,05). Hasil akhir didapatkan yang paling berhubungan dengan kejadian dismenore adalah konsumsi makanan cepat saji. Saran bagi remaja putri lebih memperluas pengetahuan tentang dismenore agar saat mengalami kejadian dismenore dapat mengatasinya.